What are the main variables that influence the dynamics of Ecuador's sovereign risk? - Paul Carrillo-Maldonado; Javier Díaz Cassou; Miguel Flores (Journal of Applied Economics, 2023)
This paper analyzes the determinants of Ecuador's sovereign spreads as measured by the EMBI index. We use Bayesian algorithms to estimate a structural vector autoregressive model with three blocks (international, regional, and domestic). Global variables drive most of the dynamics of the Ecuadorian EMBI, also influenced by the evolution of sovereign risks in other Latin American countries like Chile and Peru. We likewise show that the increase in public debt is the primary domestic variable affecting the Ecuadorian EMBI.
Keywords: 330; Blocked SVAR; EMBI; International market; Spillover effect